Response of Growth and Yield of Chili to the Doses of NPK Fertilizer Application - Puji Harsono; Devi Mei Linda Kurniawati; Aprilia Ike Nurmalasari; Eddy Tri Haryanto (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
The addition of NPK fertilizer has the potential to increase productivity. This research aims to obtain the optimum dose of compound NPK fertilizer to increase the growth and yield of chilli. This experiment was conducted in the chili fields of Sendangijo Village, Selogiri District, Wonogiri Regency, Central Java from May-September 2023. The method used was a Randomized Complete Block Design (RCBD) non factorial and four replications. The factor used dose of compound NPK (0, 50, 100, and 150 kg ha-1). The variables observed were plant height, leaf area, number of dichotomous branches, fresh and dry weight of stover, fruiting age, fruit length, number of fruits per plant, and fruit weight per plant. Data analysis was carried out using analysis of variance (ANOVA) on the level of α5%. If there is a significant difference, then further testing is done with an orthogonal polynomial test. The results showed that dose of NPK fertilizer did not show a significant effect on plant height, leaf area, number of branches, fruiting age, fruit length, number of fruits per plant and fruit weight per plant of chilli.